2017
DOI: 10.1371/journal.pone.0174627
|View full text |Cite
|
Sign up to set email alerts
|

5-aminolevulinic acid-mediated photodynamic therapy and its strain-dependent combined effect with antibiotics on Staphylococcus aureus biofilm

Abstract: Staphylococcus aureus (S. aureus) is hard to be eradicated, not only due to the emergence of antibiotic resistant strains but also because of its ability to form biofilm. Antibiotics are the major approach to treating biofilm infections, but their effects are unsatisfactory. One of the potential alternative treatments for controlling biofilm infections is photodynamic therapy (PDT), which requires the administration of photosensitizer, followed by light activation. 5-aminolevulinic acid (ALA), a natural photos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Current progress in the development of photosensitizers relies on the identification of specific design parameters. On one hand, there is an increasing appreciation of the need to integrate in molecular design insights emerging from studies of PS-target interactions, cellular signaling processes and increased resistance [ 6 , 7 ]. On the other hand, photophysical and photochemical properties of PS can be related with its behavior in biological systems, namely with aggregation, tumor type-specific PS uptake mechanisms, binding to plasma proteins or change in hydrophilicity/lipophilicity in given physiological environments.…”
Section: Introductionmentioning
confidence: 99%
“…Current progress in the development of photosensitizers relies on the identification of specific design parameters. On one hand, there is an increasing appreciation of the need to integrate in molecular design insights emerging from studies of PS-target interactions, cellular signaling processes and increased resistance [ 6 , 7 ]. On the other hand, photophysical and photochemical properties of PS can be related with its behavior in biological systems, namely with aggregation, tumor type-specific PS uptake mechanisms, binding to plasma proteins or change in hydrophilicity/lipophilicity in given physiological environments.…”
Section: Introductionmentioning
confidence: 99%
“…efflux systems), changes in the chemical microenvironment within the biofilm and even deactivation of antimicrobial agents . In addition, the reduced diffusion or neutralization of ROS by the biofilm matrix is known to decrease the penetration of light and PS to the bottom layers of biofilm , and the insufficient supply of oxygen in these deeper biofilm layers during aPDT is also suggested to play an important role in the tolerance of sessile cells to photoinactivation.…”
Section: Resultsmentioning
confidence: 99%
“…The combined treatment with ciprofloxacin and both lasers was effective against S. aureus biofilms, reducing the biofilm cell counts by 81% from its value for untreated cells and by 44% from its value for cells receiving monotherapy with ciprofloxacin (Krespi et al, 2011 ). In other studies, Barra et al ( 2015 ) and Zhang et al ( 2017 ) presented results of experiments which were conducted with the presence of delta- aminolevulinic acid and antibiotics against S. aureus . Barra et al ( 2015 ) reported a synergistic effect from the use of a combined aPDI and gentamycin treatment against three representatives belonging to Staphylococcus .…”
Section: Antimicrobial Photodynamic Inactivation Combined With Antimimentioning
confidence: 99%